Implementasi Hyper Spectral of Remote Sensing untuk Analisis Kawasan Ekowisata Mangrove Potensial di Kecamatan Tobelo Timur Menggunakan NDVI, SAVI, dan EVI - Yerik Afrianto Singgalen (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
Studies on the resilience of mangrove forest areas are becoming popular in Indonesia, despite the implementation of the Hyper Spectral of Remote Sensing method in identifying changes in vegetation index values based on the Normalized Difference Vegetation Index (NDVI), Soil Adjusted Vegetation Index (SAVI) and Enhanced Vegetation Index models (EVI) in unreached areas need to be done to add to the database so that it becomes a reference for further research. Considering this, this study uses the hyperspectral method of remote sensing through the following stages: data collection; data processing; radiometric calibration; dimension reduction; data analysis; interpretation of results. Meanwhile, the bands used have been adjusted to NDVI, SAVI, and EVI models at the dimension reduction stage. The results of this study show that the overall average value of the calculation results of NDVI, SAVI, and EVI based on Zone 1, Zone 2, Zone 3, and Zone 4 of the mangrove area of East Tobelo District indicates the condition of medium or sufficient category density and dense or dense. Thus, it can be known that the location is feasible to be developed as a tourist attraction through a community-based mangrove ecotourism area development model.